Sex differences in heart rate responses to postural provocations - Hnatkova, Katerina; Šišáková, Martina; Smetana, Peter; Toman, Ondřej; Huster, Katharina M; Novotný, Tomáš; Schmidt, Georg; Malik, Marek (International journal of cardiology, 2019)
Sex differences are known in several facets of cardiac electrophysiology, mostly concerning myocardial repolarisation. In this study, heart rate and heart rate variability (HRV) responses to postural provocations were compared in 175 and 176 healthy females and males, respectively (aged 33.1 ± 9.1 years). Two different postural provocative tests with position changes supine→sitting→standing→supine and supine→standing→sitting→supine (15-min standing, 10-min other positions) were performed up to 4 times in each subject. Heart rate and heart rate variability spectral indices were measured in 5-min windows before positional changes. At supine position, females had averaged heart rate approximately 5 beats per minute (bpm) faster than males and this sex difference was practically constant during the postural changes. In both sexes, change supine→sitting and supine→standing increased heart rate by approximately 10 and 30 bpm, respectively, with no statistical differences between the sex groups. At supine baseline, females had normalised high frequency components (nHF) of HRV approximately 7% larger compared to males (p < 0.001). While the same difference in nHF was found at sitting, the change to standing position lead to significantly larger nHF reduction in females compared to males (mean changes 22.5 vs 17.2%, p < 0.001). This shows that despite similar heart rate increase, females respond to standing by more substantial shifts in cardiac sympatho-vagal modulations. This makes it plausible to speculate that the differences in autonomic reactions to stress contribute to the known sex-differences in psychosocial responses to stressful situations and to the known difference in susceptibility to ventricular fibrillation between females and males.
Keywords: Male; Responses to stress; Autonomic Nervous System; postura těla; srdeční frekvence; Postural changes; Sex Factors; Humans; Heart rate; mužské pohlaví; Female; Reference Values; autonomní nervový systém; Autonomic responsiveness; Posture; ženské pohlaví; Sex differences; Heart Rate; mladý dospělý; Adult; Young Adult; sexuální faktory; Heart rate variability; dospělí; lidé; referenční hodnoty; Autonomic modulations